Alcohol Consumption and the Risk of Gastroesophageal Reflux Disease: A Systematic Review and Meta-analysis. (4th September 2018) - Pan, Jiaqi; Cen, Li; Chen, Weixing; Yu, Chaohui; Li, Youming; Shen, Zhe
Abstract : Gastroesophageal reflux disease (GERD) is a prevalent disease, and the incidence is rising. We conducted a meta-analysis of observational studies, indicating that there was a significant association between alcohol consumption and the risk of GERD. This finding provides important implications for the prevention and control of GERD. Abstract: Aims: Epidemiologic evidence on alcohol consumption increasing the risk of gastroesophageal reflux disease (GERD) is contradictory. This study aimed to investigate the correlation between alcohol consumption and GERD by a meta-analysis of observational studies. Short summary: Gastroesophageal reflux disease (GERD) is a prevalent disease, and the incidence is rising. We conducted a meta-analysis of observational studies, indicating that there was a significant association between alcohol consumption and the risk of GERD. This finding provides important implications for the prevention and control of GERD. Methods: Two investigators retrieved relevant studies on PubMed, Cochrane and EMBASE, respectively. The summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by random effects model to assess the association. Heterogeneity was quantified using the Q statistic and I 2 . Subgroup analysis, publication bias and sensitivity analysis were also conducted. Results: Twenty-six cross-sectional studies and three case-control studies were included in the meta-analysis. The pooled random effects OR was 1.48 (95%CI, 1.31–1.67; I 2 = 88.8%), in comparison between drinkers and non-/occasional drinkers. For reflux esophagitis and non-erosive reflux disease, two subtypes of GERD, the ORs were 1.78 (95%CI, 1.56–2.03; I 2 = 87.5%) and 1.15 (95%CI, 1.04–1.28; I 2 = 0.3%), respectively. In addition, the pooled OR for drinkers who drank <3–5 times or days per week was 1.29 (95%CI, 1.14–1.46; I 2 = 35.5%), while for those who drank more frequently, the OR was 2.12 (95%CI, 1.63–2.75; I 2 = 55.1%). Dose–response analysis showed a linear association between alcohol consumption and GERD ( P for nonlinearity = 0.235 ) . The pooled OR for a 12.5 g/day increment of alcohol was 1.16 (95%CI, 1.07–1.27; P = 0.001). Conclusions: This meta-analysis provides evidence for a potential association between alcohol drinking and the risk of GERD. The increase in alcohol consumption and frequency showed a stronger association with GERD.